The Concept of Control in Composition of Consolidated Financial Statements – Past and Present - Kamburova, Lilyana (Research Papers, 2019)
The concept of control is a key part of the theory and practice of consolidated financial statements and plays a significant role in deciding how to present the financial statements of an economic group of companies. The author consistently analyses the concept of control in consolidated financial statements in the International Accounting Standards. Also, the author reviews the development of the concept of control in the consolidated financial statements in the National Accounting Standards through a comparative analysis of the different historical stages. It can be concluded that in the National Accounting Standards the concept of control and the requirements for preparation of consolidated statements have not been changed significantly over the years, but rather they have been moved from the accounting standards to the Accounting Act and vice versa.